2009
DOI: 10.1002/bies.200800212
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between transcription factors and microRNAs in genome‐scale regulatory networks

Abstract: Metazoan genomes contain thousands of protein-coding and non-coding RNA genes, most of which are differentially expressed, i.e., at different locations, at different times during development, or in response to environmental signals. Differential gene expression is achieved through complex regulatory networks that are controlled in part by two types of trans-regulators: transcription factors (TFs) and microRNAs (miRNAs). TFs bind to cis-regulatory DNA elements that are often located in or near their target gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
194
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(207 citation statements)
references
References 105 publications
(118 reference statements)
10
194
0
1
Order By: Relevance
“…Tumor cells, where miR-146b is highly up-regulated, may well be making use of such efficient mechanisms to aberrantly exploit them favoring dedifferentiation and progression. At the genome scale level, it is well established that these regulatory circuits involving miRNAs and transcription factors are prevalent mechanisms of gene expression (44,46). The regulatory circuit miR-146b-3p-PAX8-NIS described above illustrates the importance of such regulatory miRNA-TFs pairs as examples of regulators of essential biological functions like the metabolism of iodide and ultimately dedifferentiated state in thyroid cells (Fig.…”
Section: From Cancer Genes To Signaling and Differentiation: Toward Amentioning
confidence: 97%
See 1 more Smart Citation
“…Tumor cells, where miR-146b is highly up-regulated, may well be making use of such efficient mechanisms to aberrantly exploit them favoring dedifferentiation and progression. At the genome scale level, it is well established that these regulatory circuits involving miRNAs and transcription factors are prevalent mechanisms of gene expression (44,46). The regulatory circuit miR-146b-3p-PAX8-NIS described above illustrates the importance of such regulatory miRNA-TFs pairs as examples of regulators of essential biological functions like the metabolism of iodide and ultimately dedifferentiated state in thyroid cells (Fig.…”
Section: From Cancer Genes To Signaling and Differentiation: Toward Amentioning
confidence: 97%
“…In addition, PAX8 regulates miR-146b transcription forming a regulatory negative feedback loop where PAX8 limits its own activity by inducing a repressor, miR-146b. Such a loop can result in coexpression of both components, either in steady-state levels or in oscillation (44). Therefore, the balanced expression of both components depends on additional input signals.…”
Section: From Cancer Genes To Signaling and Differentiation: Toward Amentioning
confidence: 99%
“…Previous studies have suggested an interplay between transcription factors and miRNAs in genome-wide regulatory networks. 83 Targeting of transcription factors by miRNAs could have a global impact on TLR-induced gene expression. NF-kB is the most important transcription factor in the TLR signaling pathway.…”
Section: Mirnas In Regulation Of Tlr and Rig-i Pathways Yk LI And Xy mentioning
confidence: 99%
“…Within the transcriptional and post-transcriptional trans-regulatory elements that make up gene regulatory networks, transcription factors often interact with microRNAs (miRNAs) to control gene expression [2,3]. miRNAs are post-transcriptional regulators that are expressed in a tissue-specific or developmental stage-specific manner, thereby greatly contributing to cell/tissue-specific protein expression profiles, including during lung organogenesis [4,5].…”
Section: Introductionmentioning
confidence: 99%